Hazard identification, risks assessment and risk controls of work tasks in selected tea and cocoa plantations in Malaysia - Zakaria, Mohamad Zamzami; Zainal Abidin, Emilia; Ya’acob, Nur Afifah (Universiti Putra Malaysia, 2019)
Frequent and high severity exposure to hazards can contribute to increased probability of harm among workers in agricultural sectors. Systematic risk assessment process will assist employers to mitigate risk using suitable control methods. The aim of this study was to perform Hazards Identification, Risk Assessment and Risk Control (HIRARC) in commodity-based agricultural plantation in Malaysia. This was a cross-sectional study among 74 workers in se- lected cocoa and tea plantations. All work activities performed at the plantations were video recorded and hazards were identified from interview-based questionnaire and work observations. The highest Risk Rating (RR) within work activities was harvesting characterised by prolonged standing with repetitive bending. Ergonomic hazard is the most common hazard. The outcome of this study can be used to provide information to assist employers and authorities in the management of safety and health at the selected type of plantations.